Beco da lama: formas e cores de uma plástica da vida - Façanha, Jose Marcilio de Sousa (2014)
Our research goes a remarkable setting of Natal-RN. This is a place where we find art practices and artworks territorialities building the margin of museums, art galleries and institutional galleries. Its geography includes an area popularly known as Mud Alley. Along geography that we critically about how some processes of sociability, which formed the margins of institutional fields, can, and its progeny, compose new possibilities to relate to art and artistic practices. Thinking about the dialogues and clashes that positioning the margins can offer, we investigated the role of bookstores, bars and other spaces of the Alley in the promotion and dissemination of artistic practices, focusing on how these spaces handle the work, the artists and the patrons Beco da Lama. Our integration into the search field resulted in collecting testimonials, pictures and watching expressions which, together with sensations obtained during the years of integration in that setting, help make our empirical material. To follow us methodologically this investigation, we looked at a higher frequency, a theoretical support of authors: Gilles Deleuze, Félix Guattari and Giorgio Agamben. With them compose an investigative diagram to think about the art of Alley, noting the relationship of the Alley with the established field of art, as well as towards the rest of the city. The results point to the view of a singular event that shows artistic practices writing in the margins of institutional spaces, new territoriality for contact with art. The term territoriality points to situations formed by practices, feelings, wishes, expressions, and poetic subjectivity that can tell us we are confronted with an event comprising it as the moment of realization of potentialities, desires, subjectivities and spatialities training, flocks, movements. In our case, the event while the Mud Alley Alley Arts forced us to rethink the role and the place of art and artist in Natal-RN